2020
DOI: 10.1097/md.0000000000022187
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for mild cognitive impairment

Abstract: Background: Mild cognitive impairment (MCI) is an intermediate stage between normal aging and Alzheimer disease, which is the most common form of dementia in the world. In clinical practice, traditional Chinese medicine (TCM) interventions have been administered for MCI, However, there is still uncertain about what strategy of TCM interventions treatment should be preferred in clinical practice. This study aims to evaluate the efficacy and acceptability of different TCM therapies through systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Alzheimer's Disease (AD), which is the most common dementia in the world (Wang et al, 2020). AD is a common neurodegenerative disease in the elderly and the major clinical manifestations are memory loss, learning disability and cognitive impairment (Zhang et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's Disease (AD), which is the most common dementia in the world (Wang et al, 2020). AD is a common neurodegenerative disease in the elderly and the major clinical manifestations are memory loss, learning disability and cognitive impairment (Zhang et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Although aging cannot be stopped, it is possible to slow down the rate of aging through various methods. Traditional Chinese medicine (TCM) is receiving increasing attention in the prevention and treatment of various neurodegenerative diseases (NDs) caused by aging 8–12 . Studies have shown that TCM can improve the neurocholine function of the body, protect cerebral vessels, and significantly improve the cognitive function of patients by acting on multiple tissues and multiple targets 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is receiving increasing attention in the prevention and treatment of various neurodegenerative diseases (NDs) caused by aging. 8 , 9 , 10 , 11 , 12 Studies have shown that TCM can improve the neurocholine function of the body, protect cerebral vessels, and significantly improve the cognitive function of patients by acting on multiple tissues and multiple targets. 13 , 14 Gastrodin is a phenolic glycoside isolated from the rhizome of Gastrodia elata and its tuber has been used in TCM for centuries.…”
Section: Introductionmentioning
confidence: 99%